Cytotoxicity of InP/ZnS Quantum Dots With Different Surface Functional Groups Toward Two Lung-Derived Cell Lines - Chen, Ting; Li, Li; Xu, Gaixia; Wang, Xiaomei; Wang, Jie; Chen, Yajing; Jiang, Wenxiao; Yang, Zhiwen; Lin, Guimiao (Frontiers in Pharmacology, 2018)
Although InP/ZnS quantum dots (QDs) have emerged as a presumably less hazardous alternative to cadmium-based QDs, their toxicity has not been fully understood. In this work, we report the cytotoxicity of InP/ZnS QDs with different surface groups (NH2, COOH, OH) towards two lung-derived cell lines. The diameter and the spectra of InP/ZnS QDs were characterized and the hydrodynamic size of QDs in aqueous solution was compared. The confocal laser scanning microscopy was applied to visualize the labeling of QDs for human lung cancer cell HCC-15 and Alveolar type II epithelial cell RLE-6TN. The flow cytometry was used to confirm qualitatively the uptake efficiency of QDs, the cell apoptosis and ROS generation, respectively. The results showed that in deionized water, InP/ZnS-OH QDs were easier to aggregate, and the hydrodynamic size was much greater than the other InP/ZnS QDs. All these InP/ZnS QDs were able to enter the cells, with higher uptake efficiency for InP/ZnS-COOH and InP/ZnS-NH2 at low concentration. High doses of InP/ZnS QDs caused the cell viability to decrease, and InP/ZnS-COOH QDs and InP/ZnS-NH2 QDs appeared to be more toxic than InP/ZnS-OH QDs. In addition, all these InP/ZnS QDs promoted cell apoptosis and intracellular ROS generation after co-cultured with cells. These results suggested that appropriate concentration and surface functional groups should be optimized when InP/ZnS QDs are utilized for biological imaging and therapeutic purpose in the future.